An Overview of Community Knowledge about Handling and Treatment of Pulmonary TB in the Health Center Area of Bajeng District, Gowa Regency - Muhamad Isnaini (Jurnal EduHealth, 2021)
This study aims to reveal and describe the community's knowledge about the handling and treatment of pulmonary TB in the working area of the Bajeng Health Center, Gowa Regency. The implementation of this research took place from June to July 2021. The population in this study was all people with TB in the working area of the Bajeng Health Center. The sample collection used the accidental sampling technique, while the number of samples in this study was 30 people with TB in the working area of the Bajeng Health Center. Data collection used a questionnaire and data analysis techniques used descriptive statistics. The results of the study revealed that out of the 30 respondents who were studied, 14 people (46.7%) had sufficient knowledge about the handling and treatment of pulmonary tuberculosis in the Working Area of the Bajeng District Health Center, 12 people (40%) had less knowledge, while those who have knowledge in the good category are 4 people (13.3%)